The Effect Of Work Environment And Compensation On The Performance Of Employees Of Pdam Situbondo District Through Motivation As An Intervening Variable - Suherman, Suherman; Koba Susanti, Ratna; Syahputra, Hendra (International Journal of Economics, Business and Innovation Research, 2025)
The purpose of this study is to analyze the influence of the variables of the Influence of the Work Environment and Compensation on the Performance of PDAM Employees in Situbondo Regency Through Motivation as an Intervening Variable.. By using the Partial Least Square (PLS) Structural equation model. Results of direct influence hypothesis testing using the Smart PLS 3.0 application. The work environment has a significant positive effect on motivation, compensation has a significant positive effect on motivation, the work environment has a significant positive effect on performance, compensation has a significant positive effect on performance, motivation has a significant positive effect on performance, the work environment has a significant positive effect on performance through motivation, and compensation has a significant positive effect on performance through motivation.